Coronavirus Disease 2019: Clinics, Treatment, and Prevention - Burkert, Francesco Robert; Lanser, Lukas; Bellmann-Weiler, Rosa; Weiss, Günter (Frontiers in Microbiology, 2021)
The COVID-19 pandemic, caused by a novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), emerged at the end of 2019 in China and affected the entire world population, either by infection and its health consequences, or by restrictions in daily life as a consequence of hygiene measures and containment strategies. As of September 2021 more than 231,000.000 infections and 4,740.000 deaths due to COVID-19 have been reported. The infections present with varied clinical symptoms and severity, ranging from asymptomatic course to fatal outcome. Several risk factors for a severe course of the disease have been identified, the most important being age, gender, comorbidities, lifestyle, and genetics. While most patients recover within several weeks, some report persistent symptoms restricting their daily lives and activities, termed as post-COVID. Over the past 18 months we have acquired significant knowledge as reflected by an almost uncountable number of publications on the nature of the underlying virus and its evolution, host responses to infection, modes of transmission and different clinical presentations of the disease. Along this line, new diagnostic tests and algorithms have been developed paralleled by the search for and clinical evaluation of specific treatments for the different stages of the disease. In addition, preventive non-pharmacological measures have been implemented to control the spread of infection in the community. While an effective antiviral therapy is not yet available, numerous vaccines including novel vaccine technologies have been developed, which show high protection from infection and specifically from a severe course or death from COVID-19. In this review we tried to provide an up-to-date schematic of COVID-19, including aspects of epidemiology, virology, clinical presentation, diagnostics, therapy and prevention.